Social Resilience and Mental Health Among Eritrean Asylum-Seekers in Switzerland. (January 2019) - Melamed, Sabra; Chernet, Afona; Labhardt, Niklaus D.; Probst-Hensch, Nicole; Pfeiffer, Constanze
Eritreans comprise the largest group of asylum-seekers in Switzerland. Gaining recognized refugee status can take up to 36 months, during which time asylum-seekers live in a state of legal limbo, intensifying threats to their well-being. Resilience and mental health among this population is poorly understood. We interviewed 10 asylum-seekers residing in Switzerland using qualitative, in-depth interviews. Data were analyzed using the Framework Method. Results indicated that mental health was understood as a binary state rather than a continuum and that trusted friends and family were responsible for recognizing and attempting to treat mental health problems. Pathways to care were potentially interrupted for asylum-seekers. Capital building, considered through the lens of social resilience, consisted of language learning, establishing of new individual- and community-level social networks, and proactive symbolic capital building through volunteering. We contextualize the asylum-seekers' experience into a resilience framework and offer practical recommendations for improving mental health care access.